Psycho-Affective Factors in Consecutive Interpreting - Bogucki, Lukasz; Bogucki, Lukasz; Walczynski, Marcin (Peter Lang, 2019)
The book presents a study into the trainee interpreters' and certified interpreters' subjective experience of psycho-affective factors in consecutive interpreting. In the form of four case studies, the book offers an insight in how the subjective experience of anxiety, fear, language ego/language inhibition/language boundaries, extroversion/introversion, self-esteem, motivation and stress conditions and affects consecutive interpreting performance. What emerges from the study is that the interpreter's psycho-affectivity is a continually operating and intricate mechanism which may impact on nearly all constituents of the consecutive interpreting process and that its potential causes may lie in virtually all ? even the seemingly unimportant ? aspects of the interpreting process.